Carbon capture and separation membrane and preparation method and application thereof
By forming a transition layer and a separation layer in the carbon capture separation membrane, low-molecular-weight polyethylene oxide is used to carry out in-situ polymerization with the main material and initiator, the problems of limited amount of low-molecular-weight PEO additives and poor mechanical properties are solved, and higher CO2/N2 separation performance and better pressure resistance are achieved.
Patent Information
- Application Number
- CN202411847411.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-14
AI Technical Summary
The amount of low molecular weight PEO additives in existing carbon capture separation membranes is limited, the mechanical properties are poor, and they are easily extruded under operating pressure differential, resulting in a degradation of separation performance.
By forming a transition layer and a separation layer on the base film, low molecular weight polyethylene oxide is used to undergo in-situ polymerization with the host material and initiator to form a more stable separation layer, which increases the amount of PEO added and enhances the film's pressure resistance.
The amount of PEO added is improved, the mechanical properties and pressure resistance of the film are enhanced, the membrane structure is stabilized, and the separation performance of CO2/N2 is improved.
Smart Images

Figure CN119607902A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a carbon capture separation membrane and a preparation method and application thereof, belonging to the technical field of separation membranes. Background Art
[0002] The widespread use of coal in inefficient coal-fired power plants produces a large amount of dust and CO2, becoming the largest source of CO2 emissions, exacerbating atmospheric pollution and causing serious environmental problems. Carbon capture, utilization and storage (CCUS) is a key way to reduce CO2 emissions in the atmosphere, especially when fossil fuels continue to be the main source of electricity production. Flue gas contains a large amount of CO2 with a very low partial pressure (0.04-0.13 atmospheres), which makes capture very challenging.
[0003] Membrane technology has become one of the leading technologies for CO2 capture due to its high energy efficiency, low maintenance and small footprint. The first challenge in developing industrial membranes is to design materials with excellent CO2 / N2 separation performance. One of the leading materials is polyethylene oxide (PEO) because PEO has a high affinity for CO2 (resulting in high CO2 / N2 solubility selectivity) and good segment flexibility (resulting in high CO2 diffusivity). The second challenge in developing industrial membranes is to form a thin (<1 μm) highly selective separation layer on a porous support. Current gas separation membranes are typically prepared from polymer solutions by a phase inversion process (forming monolithic asymmetric membranes) or a coating process (forming thin composite or TFC membranes).
[0004] Low molecular weight PEO is a kind of high-efficiency additive, which is not only miscible with various materials, but also can significantly improve the CO2 separation performance of the material. As reported in Peinemann's article, the addition of 50 wt% PEG 200 can increase the CO2 permeability coefficient from 71 Barrer to 151 Barrer, which is twice the intrinsic CO2 permeability coefficient of Pebax measured by them. However, the low molecular weight PEO embedded in it will weaken the interaction between the original adjacent segments of the polymer, which is easy to cause the instability of the material structure, weaken the mechanical properties of the original PEO-based material, and cause its stability after film formation to be greatly reduced. Its addition amount is also subject to great restrictions, which hinders the further improvement of membrane separation performance. In addition, it is reported that the added low molecular weight PEO is easily squeezed out under the operating pressure difference of carbon capture (1~10 barG), destroying the membrane structure and causing the separation performance to decrease, limiting the application scenarios of the membrane. On the other hand, since the molecular diameter of the low molecular weight PEO additive is smaller than the pore size of the bottom membrane, it is very easy to penetrate into the pores of the bottom membrane, causing serious "pore permeation" phenomenon, resulting in the final membrane permeability being too low and having no application value. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of limited amount of low molecular weight PEO additives and poor mechanical properties in the above-mentioned existing separation membranes for carbon capture, and to propose a method for increasing the amount of PEO added, and to make it into a composite membrane. The method can increase the amount of PEO added, and at the same time, the membrane structure is stable and has strong pressure resistance.
[0006] According to one aspect of the present application, a carbon capture separation membrane is provided, the carbon capture separation membrane comprising a base membrane, a transition layer and a separation layer being attached to the base membrane; The separation layer is prepared by in-situ polymerization of raw materials containing a main material, low molecular weight polyethylene oxide and an initiator.
[0007] Optionally, the low molecular weight polyethylene oxide is polyethylene oxide having an olefin double bond at the terminal group, and has a molecular weight of 100-1000 g / mol.
[0008] Optionally, the low molecular weight polyethylene oxide is polyethylene oxide having an olefin double bond at the terminal group, and the molecular weight is independently selected from any value among 100 g / mol, 200 g / mol, 300 g / mol, 500 g / mol, 800 g / mol, 1000 g / mol or a range between any two of the above.
[0009] Optionally, the low molecular weight polyethylene oxide is selected from at least one of polyethylene glycol monomethyl ether methacrylate, polyethylene glycol diacrylate, polyethylene glycol acrylate, polyethylene glycol dimethacrylate and polyethylene glycol monomethyl ether methacrylate.
[0010] Optionally, the main material is selected from at least one of polyether block amide and PolyActive™.
[0011] Optionally, the mass ratio of the main material to the low molecular weight polyethylene oxide is 1:0.1-10.
[0012] Optionally, the initiator is selected from azobisisobutyramidine hydrochloride and / or azobisisobutyronitrile.
[0013] Optionally, the bottom membrane includes at least one of a flat ultrafiltration membrane, a flat microfiltration membrane, a hollow fiber ultrafiltration membrane, and a hollow fiber microfiltration membrane.
[0014] Optionally, the base film includes at least one of polysulfone (PSF), polyethersulfone (PES), polyacrylonitrile (PAN), polyetherimide (PEI), polyvinylidene fluoride (PVDF), polyimide (PI), and polycarbonate (PC).
[0015] Optionally, the surface pore size of the base film is 10-2000 nm.
[0016] Optionally, the epidermal pore size of the base film is independently selected from any value of 10nm, 20nm, 30nm, 40nm, 50nm, 100nm, 200nm, 500nm, 1000nm, 1200nm, 1500nm, 1800nm, 2000nm or a range between any two of the above.
[0017] Optionally, the surface pore size of the base film is 10-100 nm.
[0018] Optionally, the surface pore size of the base film is 10-30 nm.
[0019] Optionally, the transition layer is formed by blending amino silicone oil and polydimethylsiloxane.
[0020] According to another aspect of the present application, a method for preparing the carbon capture separation membrane described above is provided, the method comprising the following steps: Step S1: coating a transition layer solution on a base film, and drying in the shade at room temperature for 20 to 240 min; heating at 40 to 120° C. for 5 to 240 min, and then taking out to obtain a base film containing a transition layer; Step S2: immersing the bottom membrane containing the transition layer in the separation layer solution, drying in the shade at room temperature for 2 to 120 min, and heating at 40 to 120° C. for 5 to 240 min to obtain a carbon capture separation membrane.
[0021] Optionally, in step S1, the transition layer solution includes polydimethylsiloxane, amino silicone oil and a solvent.
[0022] Optionally, in the transition layer solution, the concentration of dimethylsiloxane is 0.5 wt.% to 10 wt.%, and the concentration of aminosilicone oil is 2 to 10 wt.%.
[0023] Optionally, in the transition layer solution, the concentration of dimethylsiloxane is independently selected from any value of 0.5wt.%, 1wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, or a range between any two of the above.
[0024] Optionally, in the transition layer solution, the concentration of the amino silicone oil is independently selected from any value of 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, or a range between any two of the above.
[0025] Optionally, the solvent is selected from at least one of n-hexane, isooctane, n-heptane, gasoline and petroleum ether.
[0026] Optionally, in step S2, the separation layer solution includes a main material, low molecular weight polyethylene oxide, an initiator and an organic solvent.
[0027] Optionally, in the separation layer solution, the concentration of the main material is 0.5 wt.%~10 wt.%, and the concentration of the low molecular weight polyethylene oxide is 1.0 wt.%~15 wt.%.
[0028] Optionally, in the separation layer solution, the concentration of the main material is independently selected from any value among 0.5wt.%, 1wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.% or a range between any two of the above.
[0029] Optionally, in the separation layer solution, the concentration of low molecular weight polyethylene oxide is any value of 1wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, 12wt.%, 15wt.%, or a range between any two of the above.
[0030] Optionally, the concentration of the initiator is 100-10000 ppm of the total mass of the separation layer solution.
[0031] Optionally, the low molecular weight polyethylene oxide is selected from at least one of polyethylene glycol monomethyl ether methacrylate, polyethylene glycol diacrylate, polyethylene glycol acrylate, polyethylene glycol dimethacrylate and polyethylene glycol monomethyl ether methacrylate.
[0032] Optionally, the main material is selected from at least one of polyether block amide and PolyActive™.
[0033] Optionally, the initiator is selected from azobisisobutyramidine hydrochloride (V-50) and / or azobisisobutyronitrile (AIBN).
[0034] Optionally, the organic solvent is selected from at least one of an ethanol / water mixture, n-butanol, propanol, isopropanol, and tetrahydrofuran.
[0035] Optionally, in step S2, the immersion time is 5s to 30min.
[0036] Optionally, in step S2, the separation layer solution is allowed to stand and degas for 1 to 4 hours when prepared.
[0037] According to another aspect of the present application, there is provided an application of the above-mentioned carbon capture separation membrane in the field of gas separation, wherein the gas separation field includes flue gas CO2 removal, natural gas acid gas removal, synthesis gas H2 / CO2 separation, and biogas CO2 removal.
[0038] As an optional implementation method, the present application is implemented through the following technical solutions: The preparation method of the carbon capture separation membrane comprises the following steps: coating a transition layer solution on a base membrane, and drying in the shade at room temperature for 20 to 240 minutes; placing the membrane in a blast oven for further drying under heating conditions, the drying temperature being 40 to 120° C., and heating the membrane in the oven for 5 to 240 minutes before taking the membrane out; Immerse the membrane obtained in the previous step in the separation layer solution for 5s~30min, and dry it in the shade at room temperature for 1~20min; put it into a forced air oven and further dry it under heating conditions at a drying temperature of 40~120℃, and take it out after heating for 5~240min.
[0039] Before the transition layer solution is applied to the base film, the surface of the base film needs to be cleaned with deionized water to remove dust and oil stains on the surface of the base film, and then dried.
[0040] Furthermore, the preparation of the transition layer solution includes the following steps: dissolving polydimethylsiloxane PDMS (RTV615, produced by GE, with a mass ratio of components A to B of 10) and amino silicone oil in a solvent to prepare a transition layer solution, wherein the PDMS concentration in the solution is 1-10 wt.%, and the amino silicone oil concentration is 2-10 wt.%.
[0041] Furthermore, the preparation of the separation layer solution includes: dissolving the main material in an organic solvent, adding low molecular weight polyethylene oxide (PEO) and an initiator and stirring evenly, wherein the concentration of the main material is 0.5 wt.% to 10 wt.%, preferably 1.0 wt.% to 5.0 wt.%, and the initiator concentration is 100 to 10,000 ppm of the total mass of the solution, and then standing and degassing for 1 h to 4 h.
[0042] In the present invention, in the preparation of the separation layer, the reaction that occurs is that low molecular weight polyethylene oxide polymerizes under the conditions of initiator and heating. In the preparation of the separation layer, the lack of the main material will make it impossible to form a membrane. Among them, the low molecular weight polyethylene oxide (polyethylene oxide with olefin double bonds at the end group) and the initiator uniformly distributed in the main material undergo polymerization reaction under heating conditions to form a polymer segment with a higher molecular weight and more tightly entangled with the main material. Therefore, under pressure conditions, low molecular weight polyethylene oxide (polyethylene oxide with olefin double bonds at the end group) will not precipitate from the carbon capture separation membrane; if the low molecular weight polyethylene oxide does not undergo polymerization reaction, the low molecular weight polyethylene oxide will precipitate from the carbon capture separation membrane under pressure. Therefore, in the preparation process of the separation layer, the low molecular weight polyethylene oxide (polyethylene oxide with olefin double bonds at the end group), the main material and the initiator cooperate with each other and work together to solve the problem of precipitation of low molecular weight polyethylene oxide under pressure conditions.
[0043] The beneficial effects of this application include: 1) The carbon capture separation membrane method provided in this application overcomes the problems of limited amount of low molecular weight PEO additives and poor mechanical properties in separation membranes for carbon capture, and proposes a method for increasing the amount of PEO added, while making it into a composite membrane. This method can increase the amount of PEO added, while the membrane structure is stable and has strong pressure resistance.
[0044] 2) The preparation method of the carbon capture separation membrane provided in this application is simple and easy to control, can be used in gas separation processes, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 FIG. 4 is a diagram of a test device for a gas separation membrane in an embodiment of the present application.
[0046] In the figure: 1. Nitrogen cylinder; 2. Carbon dioxide cylinder; 3. Pressure reducing valve; 4. Pressure gauge; 5. Membrane evaluation tank; 6. Stop valve; 7. Soap bubble flow meter. DETAILED DESCRIPTION
[0047] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0048] Unless otherwise specified, the raw materials in the examples of this application are purchased through commercial channels, among which polyacrylonitrile (PAN) and polysulfone (PSF) bottom membranes: from Dalian Ouke Membrane Technology Engineering Co., Ltd.; DMF, ethanol, n-butanol, and n-heptane were of analytical grade and purchased from Tianjin Kemeiou; Polydimethylsiloxane PDMS (RTV 615), GE; Amino silicone oil, Xingye new silicone materials; Polyether block amide (PEBA): Arkema, product model: Pebax®1657; Polyethylene glycol monomethyl ether methacrylate (PEGMEMA: Mw ~ 560 g / mol); Polyethylene glycol monomethyl ether acrylate (PEGMEA: Mw ~ 480 g / mol), Sigma-Aldrich.
[0049] The detection method in the embodiments of the present application is as follows: like Figure 1 As shown, place the cut circular membrane into the membrane evaluation pool 5 and seal it tightly. Open the N2 gas cylinder 1 to pass N2, and at the same time open the stop valve 6 to purge the membrane feed side with N2. After 2 minutes, close the stop valve 6 and adjust the pressure reducing valve 3 so that the pressure gauge 4 shows 0.5 MPa. After the system is stable for 1 hour, use a stopwatch to test the time it takes for the soap bubble flowmeter 7 connected to the membrane permeation side to pass 5 ml and record it. Open the CO2 gas cylinder 2 and test the CO2 permeation and separation performance of the composite membrane. The test method is the same as that of N2.
[0050] Permeation rates of CO2 and N2 J Calculated by the following formula:
[0051] Where: V—the flux of permeate gas under test conditions, cm 3 ; t—test time, s; A—effective membrane area, cm 2 ; Δp—transmembrane pressure difference, cmHg; T 0 , p0—temperature and pressure under test conditions, K, cmHg; Separation coefficient of CO2 and N2 α CO2 / N2 are the permeation rates of the two gases J CO2 and J N2 Ratio of: .
[0052] Comparative Example 1 A carbon capture separation membrane disclosed in Comparative Example 1 is prepared by the following steps: (1) Clean the surface of the polyacrylonitrile (PAN) base film and dry it; (2) PDMS (RTV 615, produced by GE, with a mass ratio of components A to B of 10) and amino silicone oil were dissolved in n-heptane to prepare a transition layer solution, in which the PDMS concentration was 3 wt.%, and the amino silicone oil concentration was 10 wt.%; (3) The polyether block amide (PEBA) main material was dissolved in an ethanol / water (ethanol:water=7:3) mixed solvent to prepare a separation layer solution, wherein the PEBA concentration in the solution was 2 wt.%. Both the transition layer solution and the separation layer solution were allowed to stand for degassing for 2 h before use; (4) Immerse the base film of step (1) in the transition layer solution of step (2), take it out, and dry it in the shade at room temperature for 60 minutes. Then, put it into a forced air oven for further drying under heating conditions at a drying temperature of 80°C, and take it out after heating in the oven for 40 minutes; (5) After immersing the membrane of step (4) in the solution of step (3) for 1 min, the membrane is taken out of the solution and dried in the shade at room temperature for 2 min; (6) The membrane obtained in step (5) is placed in a forced air oven for further drying under heating conditions at a temperature of 80° C. After heating in the oven for 30 min, the membrane is taken out to obtain a separation membrane.
[0053] The above method was used to test the membrane's permeability and separation performance for pure CO2 and N2. The test results are as follows: CO2 =154.1GPU,α CO2 / N2 =58.3. The separation performance of the membrane is average, and then the membrane surface is dry, and there is no overflow on the surface after the test.
[0054] Comparative Example 2 A carbon capture separation membrane disclosed in this comparative example 2 is prepared by the following steps: (1) Clean the surface of PAN base film and dry it; (2) PDMS (RTV 615, produced by GE, with a mass ratio of components A to B of 10) and amino silicone oil were dissolved in n-heptane to prepare a transition layer solution, in which the PDMS concentration was 3 wt.%, and the amino silicone oil concentration was 10 wt.%; (3) PEBA and PEGMEMA were dissolved in a mixed solvent of ethanol / water (ethanol:water = 7:3) to prepare a separation layer solution, in which the concentration of PEBA was 2 wt.% and the concentration of PEGMEMA was 6 wt.%; both solutions were allowed to stand for degassing for 2 h before use; (4) Immerse the base film of step (1) in the transition layer solution of step (2), take it out, and dry it in the shade at room temperature for 60 minutes. Then, put it into a forced air oven for further drying under heating conditions at a drying temperature of 80°C, and take it out after heating in the oven for 40 minutes; (5) After immersing the membrane of step (4) in the solution of step (3) for 1 min, the membrane is taken out of the solution and dried in the shade at room temperature for 2 min; (6) The membrane obtained in step (5) is placed in a forced air oven for further drying under heating conditions at a temperature of 80° C. After heating in the oven for 30 min, the membrane is taken out to obtain a separation membrane.
[0055] The above method was used to test the permeability and separation performance of the carbon capture membrane for pure CO2 and N2. The test results were as follows: CO2 =347.1 GPU, α CO2 / N2 =56.1. Compared with comparative example 1, the separation performance of the membrane is good, but the membrane surface is not completely dry, and some PEGMEMA overflows from the surface after the test, and the contact part between the membrane surface and the sealing ring is damaged.
[0056] Comparative Example 3 A carbon capture separation membrane disclosed in Comparative Example 3 is prepared by the following steps: (1) Clean the surface of the polyacrylonitrile (PAN) base film and dry it; (2) PDMS (RTV 615, produced by GE, with a mass ratio of components A to B of 10) and amino silicone oil were dissolved in n-heptane to prepare a transition layer solution, in which the PDMS concentration was 3 wt.%, and the amino silicone oil concentration was 10 wt.%; (3) Dissolve the polyether copolymer amide PEBA main material and polyethylene glycol dimethyl ether (PEGDME) in an ethanol / water (ethanol: water = 7:3) mixed solvent to prepare a separation layer solution, in which the PEBA concentration is 2 wt.%, and the PEGDME concentration is 6 wt.%; add V-50 initiator at a concentration of 1000 ppm. Both the above transition layer solution and separation layer solution are allowed to stand and degas for 2 h before use; (4) Immerse the base film of step (1) in the transition layer solution of step (2), take it out, and dry it in the shade at room temperature for 60 minutes. Then, put it into a forced air oven for further drying under heating conditions at a drying temperature of 80°C, and take it out after heating in the oven for 40 minutes; (5) After immersing the membrane of step (4) in the solution of step (3) for 1 min, the membrane is taken out of the solution and dried in the shade at room temperature for 20 min; (6) The membrane obtained in step (5) is placed in a forced air oven for further drying under heating conditions at a temperature of 80° C. After heating in the oven for 30 min, the membrane is taken out to obtain a carbon capture separation membrane.
[0057] The above method was used to test the permeability and separation performance of the carbon capture membrane for pure CO2 and N2. The test results were as follows:CO2 =324.3GPU,α CO2 / N2 =57.8. Compared with Comparative Examples 1 and 2, the membrane separation performance is good, but the membrane surface is sticky, some PEGDME overflows from the surface after the test, and the contact area between the membrane surface and the sealing ring is damaged. Example 1
[0058] A carbon capture separation membrane disclosed in this embodiment 1 is prepared by the following steps: (1) Clean the surface of the polyacrylonitrile (PAN) base film and dry it; (2) PDMS (RTV 615, produced by GE, with a mass ratio of components A to B of 10) and amino silicone oil were dissolved in n-heptane to prepare a transition layer solution, in which the PDMS concentration was 3 wt.%, and the amino silicone oil concentration was 10 wt.%; (3) Dissolve the polyether copolymer amide PEBA main material and polyethylene glycol monomethyl ether methacrylate PEGMEMA in an ethanol / water (ethanol: water = 7:3) mixed solvent to prepare a separation layer solution, in which the PEBA concentration is 2 wt.%, and the PEGMEMA concentration is 6 wt.%; add V-50 initiator at a concentration of 1000 ppm. Both the transition layer solution and the separation layer solution are allowed to stand and degas for 2 h before use; (4) Immerse the base film of step (1) in the transition layer solution of step (2), take it out, and dry it in the shade at room temperature for 60 minutes. Then, put it into a forced air oven for further drying under heating conditions at a drying temperature of 80°C, and take it out after heating in the oven for 40 minutes; (5) After immersing the membrane of step (4) in the solution of step (3) for 1 min, the membrane is taken out of the solution and dried in the shade at room temperature for 20 min; (6) The membrane obtained in step (5) is placed in a forced air oven for further drying under heating conditions at a temperature of 80° C. After heating in the oven for 30 min, the membrane is taken out to obtain a carbon capture separation membrane.
[0059] The above method was used to test the permeability and separation performance of the carbon capture membrane for pure CO2 and N2. The test results were as follows: CO2 =283.7 GPU, α CO2 / N2 =60.1. The separation performance of the membrane was slightly worse than that of Comparative Example 1. The membrane surface was completely dry. Due to the polymerization reaction of PEGMEMA, the air permeability was slightly worse than that of the membrane in Comparative Example 1. However, after the test, there was no PEGMEMA overflow on the surface, and the contact part between the membrane surface and the sealing ring was not damaged. Example 2
[0060] A carbon capture separation membrane disclosed in Example 2 is prepared by the following steps: (1) Clean the surface of PAN base film and dry it; (2) PDMS (RTV 615, produced by GE, with a mass ratio of components A to B of 10) and amino silicone oil were dissolved in n-heptane to prepare a transition layer solution, in which the PDMS concentration was 3 wt.%, and the amino silicone oil concentration was 10 wt.%; (3) Dissolve PEBA and PEGMEMA in a mixed solvent of ethanol / water (ethanol:water = 7:3) to prepare a separation layer solution, in which the concentration of PEBA is 2 wt.%, and the concentration of PEGMEMA is 10 wt.%; add V-50 initiator at a concentration of 1000 ppm. Both the transition layer solution and the separation layer solution are allowed to stand and degas for 2 h before use; (4) Immerse the base film of step (1) in the transition layer solution of step (2), take it out, and dry it in the shade at room temperature for 60 minutes. Then, put it into a forced air oven for further drying under heating conditions at a drying temperature of 80°C, and take it out after heating in the oven for 40 minutes; (5) After immersing the membrane of step (4) in the solution of step (3) for 1 min, the membrane is taken out of the solution and dried in the shade at room temperature for 20 min; (6) The membrane obtained in step (5) is placed in a forced air oven for further drying under heating conditions at a temperature of 80° C. After heating in the oven for 30 min, the membrane is taken out to obtain a carbon capture separation membrane.
[0061] The above method was used to test the permeability and separation performance of the carbon capture membrane for pure CO2 and N2. The test results were as follows: CO2 =362.9 GPU, α CO2 / N2 =59.2. The separation performance of the membrane is comparable to that of Comparative Example 1, the membrane surface is completely dry, no PEGMEMA overflows from the surface after the test, and there is no damage to the contact part between the membrane surface and the sealing ring. By comparing the carbon capture separation membranes in Example 1 with those in Example 2, it can be found that increasing the amount of PEGMEMA added can improve the air permeability of the carbon capture separation membrane. Example 3
[0062] A carbon capture separation membrane disclosed in this embodiment 3 is prepared by the following steps: (1) Clean the surface of PAN base film and dry it; (2) PDMS (RTV 615, produced by GE, with a mass ratio of components A to B of 10) and amino silicone oil were dissolved in n-heptane to prepare a transition layer solution, in which the PDMS concentration was 3 wt.%, and the amino silicone oil concentration was 10 wt.%; (3) Dissolve PEBA and PEGMEMA in n-butanol to prepare a separation layer solution, in which the PEBA concentration is 2 wt.% and the PEGMEMA concentration is 10 wt.%; add AIBN initiator at a concentration of 2000 ppm. Both solutions are allowed to stand and degas for 2 h before use; (4) Immerse the base film of step (1) in the transition layer solution of step (2), take it out, and dry it in the shade at room temperature for 60 minutes. Then, put it into a forced air oven for further drying under heating conditions at a drying temperature of 80°C, and take it out after heating in the oven for 40 minutes; (5) After immersing the membrane of step (4) in the solution of step (3) for 1 min, the membrane is taken out of the solution and dried in the shade at room temperature for 2 min; (6) The membrane obtained in step (5) is placed in a forced air oven for further drying under heating conditions at a temperature of 90° C. After heating in the oven for 30 min, the membrane is taken out to obtain a carbon capture separation membrane.
[0063] The above method was used to test the permeability and separation performance of the carbon capture membrane for pure CO2 and N2. The test results were as follows: CO2 =301.8 GPU, α CO2 / N2 =62.2. The membrane surface is completely dry, no PEGMEMA overflows from the surface after the test, and there is no damage to the contact area between the membrane surface and the sealing ring. Example 4
[0064] A carbon capture separation membrane disclosed in Example 4 is prepared by the following steps: (1) Clean the surface of the polysulfone (PSF) base membrane and dry it; (2) PDMS (RTV 615, produced by GE, with a mass ratio of components A to B of 10) and amino silicone oil were dissolved in n-heptane to prepare a transition layer solution, in which the PDMS concentration was 3 wt.%, and the amino silicone oil concentration was 10 wt.%; (3) Dissolve PEBA and PEGMEMA in n-butanol to prepare a separation layer solution, in which the concentration of PEBA is 2 wt.% and the concentration of PEGMEMA is 10 wt.%; add AIBN initiator at a concentration of 2000 ppm. Both solutions are allowed to stand and degas for 2 h before use; (4) Immerse the base film of step (1) in the transition layer solution of step (2), take it out, and dry it in the shade at room temperature for 60 minutes. Then, put it into a forced air oven for further drying under heating conditions at a drying temperature of 80°C, and take it out after heating in the oven for 40 minutes; (5) After immersing the membrane of step (4) in the solution of step (3) for 1 min, the membrane is taken out of the solution and dried in the shade at room temperature for 2 min; (6) The membrane obtained in step (5) is placed in a forced air oven for further drying under heating conditions at a temperature of 90° C. After heating in the oven for 30 min, the membrane is taken out to obtain a carbon capture separation membrane.
[0065] The above method was used to test the permeability and separation performance of the carbon capture membrane for pure CO2 and N2. The test results were as follows: CO2 =311.3 GPU, α CO2 / N2 =59.4. The membrane surface is completely dry, no PEGMEMA overflows from the surface after the test, and there is no damage to the contact area between the membrane surface and the sealing ring.
[0066] use Figure 1 The pressure resistance performance was tested by using a device, and the test pressure was gradually increased (by 0.1 MPa each time, starting from 0.1 MPa) until additives overflowed from the membrane surface. The specific test results are shown in Table 1.
[0067] Table 1 Example Pressure resistance (MPa) Comparative Example 1 >1.5 Comparative Example 2 0.2 Comparative Example 3 0.2 Example 1 >1.5 Example 2 >1.5 Example 3 >1.5 Example 4 >1.5 It can be seen from Table 1 that when the separation layer solution is simultaneously added with reactive low molecular weight PEO and initiator, the pressure resistance is greatly improved, and there is no overflow of low molecular weight PEO from the membrane surface within the detection range.
[0068] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A carbon capture separation membrane, characterized in that: The carbon capture separation membrane comprises a base membrane, on which a transition layer and a separation layer are attached; The separation layer is prepared by in-situ polymerization of raw materials containing a main material, low molecular weight polyethylene oxide and an initiator.
2. The carbon capture separation membrane according to claim 1, characterized in that: The low molecular weight polyethylene oxide is polyethylene oxide having an olefin double bond at the end group and a molecular weight of 100 to 1000 g / mol; Preferably, the low molecular weight polyethylene oxide is selected from at least one of polyethylene glycol monomethyl ether methacrylate, polyethylene glycol diacrylate, polyethylene glycol acrylate, polyethylene glycol dimethacrylate and polyethylene glycol monomethyl ether methacrylate.
3. The carbon capture separation membrane according to claim 1, characterized in that: The main material is selected from at least one of polyether block amide and PolyActive™; Preferably, the mass ratio of the main material to the low molecular weight polyethylene oxide is 1:0.1-10; Preferably, the initiator is selected from azobisisobutyramidine hydrochloride and / or azobisisobutyronitrile.
4. The carbon capture separation membrane according to claim 1, characterized in that: The bottom membrane includes at least one of a flat ultrafiltration membrane, a flat microfiltration membrane, a hollow fiber ultrafiltration membrane, and a hollow fiber microfiltration membrane; Preferably, the base film comprises at least one of polysulfone, polyethersulfone, polyacrylonitrile, polyetherimide, polyvinylidene fluoride, polyimide, and polycarbonate; Preferably, the epidermal pore size of the base film is 10-2000 nm; Preferably, the transition layer is formed by blending amino silicone oil and polydimethylsiloxane.
5. The method for preparing a carbon capture separation membrane according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Step S1: coating a transition layer solution on a base film, and drying it in the shade at room temperature for 20 to 240 min; heating it at 40 to 120° C. for 5 to 240 min, and then taking it out to obtain a base film containing a transition layer; Step S2: immersing the bottom membrane containing the transition layer in the separation layer solution, drying in the shade at room temperature for 2 to 120 min, and heating at 40 to 120° C. for 5 to 240 min to obtain a carbon capture separation membrane.
6. The preparation method according to claim 5, characterized in that: In the step S1, the transition layer solution includes polydimethylsiloxane, amino silicone oil and solvent; Preferably, in the transition layer solution, the concentration of dimethylsiloxane is 0.5 wt.% to 10 wt.%, and the concentration of aminosilicone oil is 2 to 10 wt.%; Preferably, the solvent is selected from at least one of n-hexane, isooctane, n-heptane, gasoline and petroleum ether.
7. The preparation method according to claim 5, characterized in that: In the step S2, the separation layer solution includes a main material, low molecular weight polyethylene oxide, an initiator and an organic solvent; Preferably, in the separation layer solution, the concentration of the main material is 0.5 wt.%~10 wt.%, and the concentration of the low molecular weight polyethylene oxide is 1.0 wt.%~15 wt.%; Preferably, the concentration of the initiator is 100-10000 ppm of the total mass of the separation layer solution.
8. The preparation method according to claim 7, characterized in that: The low molecular weight polyethylene oxide is selected from at least one of polyethylene glycol monomethyl ether methacrylate, polyethylene glycol diacrylate, polyethylene glycol acrylate, polyethylene glycol dimethacrylate, and polyethylene glycol monomethyl ether methacrylate; Preferably, the main material is selected from at least one of polyether block amide and PolyActive™; Preferably, the initiator is selected from azobisisobutyramidine hydrochloride and / or azobisisobutyronitrile; Preferably, the organic solvent is selected from at least one of ethanol / water, n-butanol, propanol, isopropanol and tetrahydrofuran.
9. The preparation method according to claim 5, characterized in that: In step S2, the immersion time is 5s to 30min; Preferably, in step S2, the separation layer solution is allowed to stand and degas for 1 to 4 hours when prepared.
10. Use of the carbon capture separation membrane according to any one of claims 1 to 4 in the field of gas separation, characterized in that: The gas separation field includes flue gas CO2 removal, natural gas acid gas removal, synthesis gas H2 / CO2 separation, and biogas CO2 removal.